TREE CULT IN TURKISH CULTURE AND ITS AFFECTS TO SHORIAN HEROIC EPICS - Mehmet Emin BARS (Fırat University, 2019)
Cult is to show respect to the god or the creatures that had supernatural powers which were accepted as the god, to take words and actions which state the adoration and dependance to them. Cult is seen in all the religions from primitive beliefs to